In Silico Drug Design for Mycobacterium tuberculosis and Development of Host–Pathogen Interaction Network and Molecular Docking Procedures - Keerthana S (International Journal of Molecular Biotechnological Research, 2023)
Objective: A leading cause of illness is the contagious disease tuberculosis (TB), this infection with Mycobacterium tuberculosis complex (MTBC) particularly M. tuberculosis and M. africanum, is what causes tuberculosis. Diverse receptor proteins (mycobacterial proteins) with various 3D structures and functions were evaluated to access the multi-domain antimycobacterial action of ligands. The specific receptor proteins PDB ID: 3PTY, PDB ID: 4OW8, PDB ID: 5KWA, and PDB ID: 3ZXR, were opted for this study to determine the antimicrobial activity and general suppression of the target bacteria. Method: In this research, Arabinosyltransferase C (3PTY), protein kinase A (4OW8), Proteasomal ATPase (5KWA), and Glutamine synthetase (3ZXR) with 50 phytocompounds and their derivatives were nominated for determining the binding affinity with target proteins. This process was carried out computationally, proteins were generated from PDB, and phytocompounds were generated from PubChem. Purification of target proteins by BIOVIA for Molecular docking which is tendered by PyRx and visualization of the 3D structures of target proteins with ligands by BIOVIA. Physiological screening of ligands by ADMETlab 2.0 and generation of Ramachandran plots and Hydrophobicity by BIOVIA and PDBsum Generate. Result: In this study, after the experimental analysis with different bioinformatics tools and software, 13 bioactive ligands with the greatest satisfactory interaction properties were chosen from 50 that are docked with the four different target Mycobacterium proteins in this investigation. Conclusion: Using computational and bioinformatics methodologies, plant anti-MTB phytocompounds with specific combating activity against particular target proteins have been outlined, and the target protein with advantages associated has been discovered.
Keywords: ADMET analysis; Contagious; diverse; molecular docking; purification; suppression; visualization